REFLECTIVE THINKING PROFILE OF JUNIOR HIGH SCHOOL STUDENTS IN THE TOPIC OF THE HUMAN REPRODUCTIVE SYSTEM: A QUANTITATIVE DESCRIPTIVE STUDY - Ruganda, Ernita; Surahman, Endang; Badriah, Liah; Hernawati, Diana (Universitas Tanjungpura, 2026)
Reflective thinking constitutes a critical 21st-century competency aligned with the demands of Society 5.0 and the implementation of the Merdeka Curriculum. This study maps the reflective thinking profile of 31 ninth-grade students at SMPN 2 Singaparna on the topic of the human reproductive system through a quantitative descriptive analysis using the Reflective Thinking Questionnaire (RTQ) adapted from Kember et al. (2000). The results indicate an overall mean score of 3.54 (moderate category), with habitual action as the lowest dimension, understanding and reflection categorized as high, and critical reflection as moderate. These findings underscore the necessity of instructional strategies that integrate reflection at every stage of the learning process. The study recommends the development of a Problem-Based Learning model grounded in a deep learning approach as an alternative to strengthen junior high school students’ critical and reflective thinking skills.